Reliability and criterion-related validity of the 20-yard shuttle test in competitive junior tennis players - Eriksson, A.; Johansson, F. R.; Bäck, M. (Open Access Journal of Sports Medicine, 2015)
Purpose: This study adds to the previous work in the field of sport-specific fitness testing by evaluating a tennis-specific agility test called "the 20-yard shuttle test". The aim of the study was to evaluate the test-retest reliability, the inter-rater reliability, and the criterion-related validity of the 20-yard shuttle test on competitive junior tennis players. Participants and methods: Totally, 34 Swedish tennis players (13 girls), mean age 14±1.6 years, participated in the study. To examine test-retest reliability, the subjects performed the 20-yard shuttle test three times on the same day and then the same procedure was repeated after 3 days. To test the inter-rater reliability, the time was measured with a stopwatch simultaneously by two different raters. The time recorded manually was compared to the gold standard of digital timing to evaluate the criterion-related validity. Results: Excellent test-retest reliability was found both within the same day (intraclass correlation coefficient [ICC] 0.95) and between days (ICC 0.91). Furthermore, the results showed excellent inter-rater reliability (ICC 0.99) and criterion-related validity on both test occasions (ICC 0.99). Conclusion: We have provided introductory support for the 20-yard shuttle test as a reliable and valid test for use in competitive junior tennis players. The ease of administration makes this test a practical alternative to evaluate physical fitness in order to optimally train the athletes.